Could the Theory of Planned Behaviour Explain Market Discipline in Sharia Mutual Funds? - Umi Widyastuti; Erie Febrian; Sutisna Sutisna; Tettet Fitrijanti (Australasian Accounting, Business and Finance Journal, 2023)
A significant number of studies have explored market discipline as indicated by investors or customers being sensitive toward the excessive risks taken by banks. Yet no scholars have sought to review this topic from the behavioural finance perspective. This study defines market discipline as withdrawal behaviour, captured here using the theory of planned behaviour (TPB) as one of the behavioural finance theories. This study aims to determine the psychological and social factors influencing market discipline from a behavioural perspective, by employing the TPB. This study’s sample comprised of 93 academicians who invested in Sharia mutual funds in Greater Jakarta, Indonesia. The results show that the intention to withdraw and perceived behavioural control (PBC) are able to predict the market discipline, while the intention to withdraw from Sharia mutual funds is determined by the subjective norms and PBC. Attitudes towards withdrawal are shown to be insignificant in explaining the intention to withdraw from Sharia mutual funds.
Keywords: Market discipline; Behavioural perspective; Academicians; Sharia mutual fund